The Effectiveness of Using Google Classroom in Learning Islamic Religious Education Subjects at SMAN 1 Sliyeg - Arip Wibowo; Muhammad Zidan M. (Konsultan Jurnal Ilmiah Indonesia, 2025)
Islamic Religious Education lessons require a lot of learning skills or practices that will later be able to support students' abilities in implementing them in life. However, the current conditions with the endless pandemic require teachers to remain active in seeking information on media and platforms that are still able to support the learning process of students. Because learning that was previously able to be done face-to-face must now switch to online learning, which of course requires new habits in the scope of learning at school. One platform that greatly supports student learning is Google Classroom. The purpose of this study was to determine how effective Google Classroom is in helping teachers in the learning process for students of SMAN 1 Sliyeg, in addition to knowing how much influence learning has when using Google Classroom which requires understanding in its use and whether there is a difference with learning through Google Classroom from the side of students and teachers of subjects, especially in Islamic Religious Education subjects. This study uses a qualitative case study research method which focuses on researching the conditions of students with the use of Google Classroom in learning. The form of this research was carried out using field observations, interview techniques, questionnaires, and documentation. Effectiveness of Using Google Classroom in Islamic Religious Education at SMA N 1 Sliyeg from the interview information obtained by researchers, the lack of technological knowledge is one of the obstacles for teachers to start using other educational media during online learning at this time. The problems or problems that arise from student participants in online learning have indeed been predicted in advance. This is because with online education there are many aspects that need to be considered to support online learning activities so that they can run smoothly.